THE IMPACT OF CARBON EMISSION DISCLOSURE ON CORPORATE REPUTATION AND FINANCIAL PERFORMANCE - Triasma, Citra; Sari, Rela (LP2M IBK Nitro, 2025)
This study examines the impact of carbon emission disclosure on corporate reputation and financial performance. Carbon emission disclosure is considered a form of transparency and accountability of companies towards environmental issues, which can indirectly influence the company’s image and financial performance. Using a qualitative approach with a literature review method, this research collects and analyzes several secondary sources from international journals, books, and reports from relevant institutions. The analysis results indicate that carbon emission disclosure, when conducted transparently and comprehensively, can enhance a company's reputation by strengthening stakeholder trust and consumer loyalty. On the other hand, such openness encourages companies to optimize operational efficiency, reduce costs, and attract investment, thus contributing positively to long-term financial performance. These findings highlight the importance of integrating carbon emission disclosure into business strategies as a risk management tool and an effort to enhance corporate sustainability.